An online feedback system for laparoscopic training during the COVID-19 pandemic: evaluation from the trainer perspective. Issue 8 (August 2022) - Kuboki, Daigo; Kawahira, Hiroshi; Maeda, Yoshitaka; Oiwa, Kosuke; Unoki, Teruhiko; Lefor, Alan Kawarai; Sata, Naohiro
Abstract: Objective: A system to provide feedback for laparoscopic training using an online conferencing system during the COVID-19 pandemic was developed. The purpose of this study is to evaluate this system from the trainer perspective. Design: A procedural feedback system using an online conferencing system was devised. Setting: Surgical training was observed using an online conferencing system (Zoom). Feedback was provided while viewing suture videos which are, as a feature of this system, pre-recorded. Feedback was then recorded. Trainer comments were then converted into text, summarized as feedback items, and sorted by suture phase which facilitates reflection. Trainers completed a questionnaire concerning the usability of the online feedback session. Results: Eleven trainers were selected. Physicians had an average experience of 21.9 ± 5.9 years (mean ± standard deviation). The total number of feedback items obtained by classifying each phase was 32. Based on questionnaire results, 91% of trainers were accustomed to the use of Zoom, and 100% felt that online procedural education was useful. In questions regarding system effectiveness, more than 70% of trainers answered positively to all questions, and in questions about efficiency, more than 70% of trainers answered positively. Only 55% of the trainers felt that this system was easy to use, but 91% were satisfied as trainers. Conclusions: The results of the questionnaire suggest that this system has high usability for training. This online system could be a useful tool for providing feedback in situations where face-to-face education is difficult. Abstract : Laparoscopic surgery, Online feedback system, Usability, Subjective evaluation, COVID-19.